COMPARISON OF DIETARY PRACTICES AND BODY MASS INDEX AMONG EDUCATED HOUSEWIVES AND WORKING WOMEN IN KARACHI - Raza, Lubna; Ali, Tahira Mohsin; Hasnain, Abid (Journal of Ayub Medical College Abbottabad, 2017)
Background: BMI is considered as a major determinant of health. The objective of study was to find out differences between dietary practices, as well as BMI in educated housewives and working woman. It is supposed that both study groups may have difference in work pressures with resultant diverse preferences for food. This can affect health status particularly in relation to obesity in women. Furthermore, we selected participants with 14 years education expecting basic awareness of healthful diet. Methods: This cross sectional study had a convenient sampling method and sample size of 600 with 300 house wives and 300 working women, aged 35-45 years. Dietary habits were recorded by interview. BMI was calculated by standard formula, and results obtained by Chi-Square using SPSS 17. Results: Working women had healthier dietary practices. Number of meals, fruits, fish/ poultry and water consumption was better in working mothers with significant p value < 0.00.1. Intake of vegetables and fast food was found similar. BMI comparison showed that majority of housewives were noted as overweight whereas working women showed normal weight, p-value=< 0.001. Most housewives responded that they have a sedentary life style as opposed to working women p- value < 0.001. Self- assessment of diet quality was comparable as it was mentioned moderate by most of the participants, however more working females accepted that they need to improve their diet and would need expert advice. Conclusion:Healthier BMI, active life style and better dietary habits were witnessed in working women as compared to housewives. Background: Body Mass Index (BMI) is considered as a major determinant of health. The objective of study was to find out differences between dietary practices, as well as BMI in educated housewives and working woman. It is supposed that both study groups may have difference in work pressures with resultant diverse preferences for food. This can affect health status particularly in relation to obesity in women. Furthermore, we selected participants with 14 years' education expecting basic awareness of healthful diet. Methods: This cross-sectional study had a convenient sampling method and sample size of 600 with 300 house wives and 300 working women, aged 35-45 years. Dietary habits were recorded by interview. Body Mass Index was calculated by standard formula, and results obtained by Chi-Square using SPSS-17. Results: Working women had healthier dietary practices. Number of meals, fruits, fish/ poultry and water consumption was better in working mothers with significant p value <0.00.1. Intake of vegetables and fast food was found similar. BMI comparison showed that majority of housewives were noted as overweight whereas working women showed normal weight (p-value <0.001). Most housewives responded that they have a sedentary life style as opposed to working women p-value <0.001. Self- assessment of diet quality was comparable as it was mentioned moderate by most of the participants, however more working females accepted that they need to improve their diet and would need expert advice. Conclusion: Healthier BMI, active life style and better dietary habits were witnessed in working women as compared to housewives. Keywords: Body Mass Index (BMI); Dietary habits; Housewives; Working women